Pengaruh Pemberian Pakan Buatan dengan Sumber Protein yang Berbeda Terhadap Efisiensi Pakan, Laju Pertumbuhan, dan Kelulushidupan Benih Abalone Hybrid - Kuncoro, Aziz; Sudaryono, Agung; Suminto, - (Journal of Aquaculture Management and Technology, 2013)
Feeding with artificial feeds in the abalone aquaculture is rarely conducted by abalone farmers. Feeding with artificial feed in the abalone aquaculture is rarely conducted by abalone farmers. Feeding with artficial feed in different protein sources is expected to produce a better quality abalone. This research aimed to determine the effects of different protein sources in artificial feeds on the on levels of feed intake, feed efficiency, growth rate and survival rate of hybrid abalone seeds and to know the best protein sources.This research used an experimental by using a completely randomized design (CRD) with 4 treatments, in 4 replicates, respeatively. The seeds of hybrid abalone used in this research were with average length size of 2,5 ± 0,08 cm and average weight sized of 3,12 ± 0,28 g. The treatments were (A) Awabi commercial feed from Japanese product; (B) feed with 100% from animals sources; (C) feed with 100% from vegetables sources; and (D) feed combination with 50% animals and 50% vegetables sources. This research was conrried in in November 2012 - January 2013 at Marine Culture Instute of Lombok. The results of this research indicated that feeding abalone with different protein sources was signifantly different (P<0,05) on levels of feed intake, highly significant effect (P<0,01) on the feed utilization efficiency and growth rate but no significant affect (P≥0,05) was observed on the survival rate of hybrid abalone seeds. Awabi feed from Japanese product performed the best effect on the growth of hybrid abalone.